The obligatory Exerciser - Assessing an overcommitment to exercise - Draeger, J.; Yates, A.; Crowell, D. (The Physician and Sportsmedicine, 2005)
A small group of patients are overly committed to their exercise routines, possibly to the detriment of their physical and psychological well-being. The concept of obligatory exercise is difficult to define, and its prevalence has not been extensively studied. Clinicians who are aware of behavioral and personality descriptors for obligatory exercisers can identify the problem and suggest treatment options. Treatment may follow guidelines similar to those for overtraining, addiction, compulsion, and eating disorders. Preventive measures lie in understanding exercisers' attitudes and beliefs about exercise and their bodies.